Analisis Peran Manajerial Pengurus Ikatan Bidan Indonesia (IBI) dalam Pelaksanaan Program Peningkatan Pemberian Asi (PPASI) di Wilayah Kota Pontianak - Dini Fitri Damayanti; Bagoes Widjanarko; Cahya Tri Purnami (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Breastfeeding improvement (PPASI) program was an effort to increase the coverage of exclusive breastfeeding. Successfulness of the exclusive breastfeeding required support from midwives. Indonesian Midwifery Association (IBI), as a midwives professional organization, had declared to implement PPASI program step by step and continually by all IBI board members. Although IBI boards at Pontianak branch had conducted several seminar activities regarding breastfeeding and lactation management training for IBI members but private practice midwives were still giving formula milk to the newborns. Based on that problem, this study was conducted with the objective to explain managerial role of IBI boards in implementing PPASI program in the area of Pontianak city. This was a qualitative study using phenomenology approach. Study informants were IBI branch and sub branch board members in the area of Pontianak city. Data were collected by in-depth interview and analyzed using content analysis method. Results of the study showed the roles of IBI boards as leader in implementing PPASI program in the motivational activities. IBI boards reminded IBI members to do lactation management in every informal small group social gathering (arisan). Evaluation of lactation management was conducted by IBI boards because they were on duty as midwives coordinators at Puskesmas and as room chiefs in hospitals. Guidance to the members was conducted by the boards through ‘arisan’ and there was no rewards given to members who had implemented lactation management. The role of boards as information resource was done by conducting lactation seminars for IBI members and in collaboration with district health office to implement lactation management training. There was no special standard for lactation management and socialization was only given to the members who wanted to apply for private practice midwives (BPS) permit. In term of IBI board role as policy makers, the board had not made planning for PPASI program. Planning and organizing were only done for seminar activities about breastfeeding. No written regulation issued by IBI board and no sanction was assigned to the members in implementing PPASI program. Based on the study results, it was suggested to IBI board to formulate evaluation format and to give rewards to IBI members in order to motivate them to implement lactation management, to make specific standard operating procedure for lactation management and to make understandable and details regulations regarding PPASI program implementation, to assign sanction to members who broke the rules.